Respuesta :
Answer:
x=0, y=0
x=2, y=4
Step-by-step explanation:
- x^y= y^x
- y= 2x
- x^(2x)= (2x)^x
- (x^2)^x= (2x)^x
- x^2=2x
- x(x-2)=0
- x=0 ⇒ y=0
- x=2 ⇒ y=4
Answer:
x = 2, y = 4.
Step-by-step explanation:
x^y = y^x
Substitute y = 2x in the above:
x^2x = (2x)^x
x^2x = 2*x * x^x Divide both sides by x^x:
x^2x / x^x = 2*x
x^(2x-x) = 2^x
x^x = 2^x
So x = 2.
and y = 2x = 4.
We can also make x = 0 and y = 0 but
I'm not sure if this result is valid because 0^0 is undefined.
Looking further into this there seems to be different opinions on this with some mathematicians say 0^0 = 1, so x=0, y = 0 may be acceptable.